Equity by design: integrating a Deprivation Index into digital platforms for breast cancer and chronic disease prevention—lessons from the ELISAH project - Ussai, Silvia; Bergé, Arantza Sanvisens; Spyratou, Ellas; Pasanisi, Patrizia; Boffi, Roberto; Mosora, Mykhailo; Tagliabue, Giovanna; Borgini, Alessandro; Contiero, Paolo (Frontiers in Public Health, 2025)
BackgroundSocio-economic inequalities are a major determinant of chronic disease risk and access to preventive services. Deprivation indices can quantify these disparities, but very few studies have considered them when examining the relationship between breast cancer incidence, prognosis, and particulate matter as a potential effect modifier. Moreover, these indices have rarely been used as active tools in service delivery. Digital health technologies offer an opportunity to embed equity into chronic disease prevention through the real-time integration of socio-economic metrics. The ELISAH project developed a digital prevention framework that incorporates a Deprivation Index to support strategies targeting breast cancer and other chronic diseases.MethodsA descriptive, policy-oriented analysis was conducted using the ELISAH framework as a case study. Nationally validated Deprivation Indices were embedded into the ELISAH platform, which integrates socio-economic, demographic, environmental, and behavioral data. A conflict-sensitive version was developed to address the needs of internally displaced populations and service disruptions in fragile health systems. The Index was configured to support both population-level equity mapping and individual-level tailoring of preventive interventions.ResultsThe Deprivation Index has been technically integrated into the digital platform and piloted in both urban and conflict-affected settings. Early implementation confirmed the feasibility of harmonizing socio-economic indicators with digital engagement data and environmental exposures. The platform’s architecture enables dynamic monitoring of inequalities and the implementation of adaptive prevention strategies. While comprehensive outcome data are pending full-scale deployment, pilot mapping has established proof-of-concept for embedding equity into digital health systems by design.DiscussionEmbedding a Deprivation Index within a digital prevention platform demonstrates how equity can be incorporated into both policy-oriented observational studies and as an active design principle. This dual application supports personalized interventions and real-time, equity-driven resource allocation. The ELISAH approach highlights the potential of digital health tools to address socio-economic and conflict-related disparities in chronic disease prevention.ConclusionIntegrating a Deprivation Index into digital prevention systems offers a scalable model for addressing health inequalities in chronic disease management. The ELISAH framework demonstrates the feasibility of making equity a foundational element of digital platforms, enabling personalized prevention, informed policy planning, and improved resilience in both stable and crisis-affected health systems.